PERANCANGAN DAN PEMBUATAN PROGRAM UNTUK MENGHILANGKAN EFEK BACKLIGHT DALAM SEBUAH IMAGE DI LUAR RUANGAN BERDASARKAN TEORI RETINEX - Kevin Pangestu; Kartika Gunadi (Jurnal Infra, 2014)
A lot of digital images processing methods that were developed to meet the needs of digital image processing which began to appear in various fields of science. In outdoors image retrieval, often arise problems, the backlight effect, that caused the digital image processing became more difficult. Therefore digital image processing applications will be made to meet the above requirement, which is based on retinex theory.Retinex is algorithm to eliminate the effects of illumination light from front/rear, and repair colors in digital image by eliminating color lighting that can make changes in digital image. In this study, digital image processed by retinex and then flatten the contrast with histogram equalization technique to eliminate the backlight effect on the digital image. Based on the test results, the application can display digital images with the backlight effect is reduced and the detail is more visible in the area that covered with the backlight shadow. In another test with images that have no backlight and bright, after the retinex process, the results is not satisfying, the images are broken, fade color and the color changes significantly.